USE OF FREE TIME FOR THE ELDERLY OF THE COMMUNITY OF THE VILLAGE OF BARCA IN THE CITY OF BELÉM-PA REGISTERED IN THE PROJECT FAMAZ LEISURE STREETS (Fiep Bulletin - online, 2016)
In recent decades, the world's attention has been directed to the problems derived from the demographic changes that result in the aging of the population. In today's world, little has free time, due to overload of work and dedication to professional qualification to meet the increasingly demanding market and competitive; soon, little dedicated time for leisure activities. This study aims to identify the main principal activities practiced in the free time by elderly residents of the community of the village of Barca, the city of Belém-PA, registered in the Famaz leisure Streets Project. To this end, we used a sample comprising 08 (eight) elderly participants, residents of this community, registered in the Famaz leisure Streets Project. All the participants signed an informed consent for participation in scientific research. As a result, verify that in relation to artistic activities, the vast majority of respondents practice cooking, representing a total of 62.5%. Regarding the cultural activities, 62.5% of respondents tend to listen to music in his spare time. Intellectual activities, 62.5% of respondents practice reading. In relation to social activities, 100% of respondents attend religious groups and family reunions; 87.5% attend meetings with friends in their spare time; in relation to everyday activities, the vast majority of respondents indicated sleep, representing 75% of the sample. When it comes to physical activities, only 25% of respondents practice the walk and the reason reported was the lack of guidance and appropriate follow-up. It is concluded that it is necessary to take physical education professionals to these communities to promote the inclusion of seniors in healthy practices of the use of their free time, in poor communities of large cities of the Brazilian territory.
Keywords: Leisure; Free Time; Elderly.